2013
DOI: 10.1111/tmi.12041
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of a general primary care package for HIV‐infected adults to an HIV centre setting in Gaborone, Botswana

Abstract: Abstractbackground As life expectancy of HIV-infected patients improves due to antiretroviral treatment (ART) and the importance of associated co-morbidities and chronic diseases increases, preventive care will become increasingly important. Adaptation of existing preventive guidelines to local environments will become a priority for HIV treatment programmes.methods Guidance from the World Health Organization, a focused evidenced-based literature review, Botswana national guidelines, Botswana-specific morbidit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 58 publications
0
17
0
Order By: Relevance
“…However, the potential benefits of an integrated approach to medical care for PLWH in SSA and other resource-limited settings could be profound, and support for this approach has been fast-growing [ 20 , 124 126 ]. The established and expanding HIV infrastructure could be an ideal foundation on which to build additional interventions and management strategies for other chronic diseases [ 29 , 127 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the potential benefits of an integrated approach to medical care for PLWH in SSA and other resource-limited settings could be profound, and support for this approach has been fast-growing [ 20 , 124 126 ]. The established and expanding HIV infrastructure could be an ideal foundation on which to build additional interventions and management strategies for other chronic diseases [ 29 , 127 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, only 5% of selected studies (n = 1) was a randomized controlled trial (RCT)—a pragmatic cluster RCT [19]. Most studies were either descriptive, cross sectional studies (n = 8) [20, 21, 22, 23, 24, 25, 26, 27] or observational cohort studies (n = 6) [21, 28, 29, 30, 31] (See S1 Dataset )…”
Section: Resultsmentioning
confidence: 99%
“…Of the 20 studies that were included after full-text review, only four studies conducted feasibility studies of an integrated CVD and HIV care intervention (See Table 2 ). Most of the studies (n = 16) reported on feasibility of integrated CVD-HIV care interventions in summary text with statements such as: the intervention ‘is feasible…’ [19, 20, 21, 22] ‘…can be utilized’ [28], and ‘ … can increase healthcare access’ [32] (See Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations